Evaluation of Medical Care for Diabetic and Hypertensive Patients in Primary Care in Mexico: Observational Retrospective Study - Agustin Lara-Esqueda; Sergio A. Zaizar-Fregoso; Violeta M. Madrigal-Perez; Mario Ramirez-Flores; Daniel A. Montes-Galindo; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; José Guzman-Esquivel; Carmen Meza-Robles; Gabriel Ceja-Espiritu; Pablo A. Kuri-Morales; Josuel Delgado-Enciso; et al. (Journal of Diabetes Research)
Introduction. The present study evaluated the quality of medical care for patients diagnosed with diabetes mellitus (DM), hypertension (HBP), and both pathologies (DM+HBP) within a public health system in Mexico. Methods. 45,498 patients were included from 2012 to 2015. All information was taken from the electronic medical record database. Each patient record was compared against the standard to test the quality of medical care. Results. Glycemia with hypertension goals reached 29.6% in DM+HBP, 48.6% in DM, and 53.2% in HBP. The goals of serum lipids were reached by 3% in DM+HBP, 5% in DM, and 0.2% in HBP. Glycemia, hypertension, and LDL cholesterol reached 0.04%. 15% of patients had an undiagnosed disease. Clinical follow-up examinations reached 20% for foot examination and clinical eye examination. Specialty referrals reached 1% in angiology or cardiology. Conclusion. Goals for glycemic and hypertension reached 50% in the overall population, while serum lipids, clinical follow-up examinations, and referral to a specialist were deficient. Patients who had both diseases had more consultations, better control for hypertension and lipids, but inferior glycemic control. Overall, quality care for DM and/or HBP has not been met according to the standards.